Rethinking Security for Internet Routing. - LYCHEV, ROBERT; SCHAPIRA, MICHAEL; GOLDBERG, SHARON (Communications of the ACM, 2016)
The article examines security measures for the Internet's Border Gateway Protocol (BGP) which establishes Internet connectivity by creating routes between independently operated networks. It explains how BGP attacks can cause network Internet traffic to be rerouted to networks run by the attackers. The article goes on to discuss BGP security protocols based on quantitative analysis.